Design of statically indeterminate reinforced glass beams: accounting for system action. Issue 5 (22nd October 2018) - Martens, Kenny; Caspeele, Robby; Belis, Jan
ABSTRACT: Transparency has become a trend in architecture. In the near future, the scale of application of structural glass will grow from elements (beams, columns, etc.) to entire systems (floors, roofs, façades, frames, etc.). Especially beams, being one of the most important and common building components, will be combined into load‐carrying systems (e. g. a supporting grid for floors and roofs). However, this scale‐up cannot be realized without incorporating structural safety and robustness on an element and system level, as required by modern building codes. For glass beams, research resulted in the concept of hybrid glass beams, in which a glass web is combined with flanges or reinforced with another material that provides post‐fracture strength and ductility, hence providing structural element safety and robustness. Especially the stainless steel reinforced glass beam, based on the principle of reinforced concrete, proved satisfactory. To investigate the feasibility of applying this concept in innovative beam systems, experimental five‐point bending tests on 3.0 m beams and membrane action tests on 4.3 m beams were performed, resulting in satisfactory load‐carrying behaviour with significant stress redistribution due to plastic hinge formation and membrane action, both compressive and tensile. Both features/mechanisms resulted in significant increases in the post‐fracture capacity of the beam systems. For the latter's design, focusing only on glass fracture is insufficient, as the element and system safety requirements should also be satisfied. Therefore, post‐fracture capacity and ductility should be incorporated in design. The latter requires an amount of reinforcing material, which decreases the beam's overall transparency. Therefore it is important that design aims at achieving maximum capacity and ductility with as little reinforcing material as possible. This paper investigates the effect of stress redistribution and membrane action on the achievable capacity of a reinforced glass beam system. It is concluded that both features/mechanisms, and especially membrane action can make a significant contribution to the ultimate capacity and ductility of the beam system. This paper also considers the incorporation of these mechanisms in design, resulting in optimal (i.e. minimal) usage of materials. Compared to statically determinate beams, a decrease in reinforcing material is possible, resulting in ever more transparent structures.